2019
DOI: 10.1111/ijcp.13432
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gene polymorphisms on postprandial triglyceride response after oral fat tolerance test meal in patients with diabetes mellitus

Abstract: Summary Aims We evaluated the influence of CETP (rs5882 and rs708272), APOE (rs7412, rs429358) and LPL (rs328) gene polymorphisms on triglyceride (TG) response to oral fat tolerance test (OFTT) meal in patients with well‐controlled type 2 diabetes mellitus (T2DM). Methods Fifty‐one men underwent OFTT and according to postprandial TG response patients were divided into two subgroups (positive [TG ≥ 220 mg/dL, 31 patients] and negative [TG < 220 mg/dL, 20 patients]). All patients were genotyped, and study varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(87 reference statements)
0
2
0
Order By: Relevance
“… 17 Gavra and colleagues, through the study on T2DM, observed that the carriers of the LPL SX genotype had significantly more negative oral fat tolerance test response (TG postprandial). 18 However, the studies of Evans et al 19 and Shahzad et al 10 illustrated that the SX genotype of the LPL S447X was not associated with hyperlipidemia. The LPL S447X polymorphism cannot affect the catalytic activity of the LPL; however, this polymorphism might result in higher concentration and the activity of the LPL enzyme.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 17 Gavra and colleagues, through the study on T2DM, observed that the carriers of the LPL SX genotype had significantly more negative oral fat tolerance test response (TG postprandial). 18 However, the studies of Evans et al 19 and Shahzad et al 10 illustrated that the SX genotype of the LPL S447X was not associated with hyperlipidemia. The LPL S447X polymorphism cannot affect the catalytic activity of the LPL; however, this polymorphism might result in higher concentration and the activity of the LPL enzyme.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, TG levels were higher at baseline and postprandially in individuals with T2DM 17 . Gavra and colleagues, through the study on T2DM, observed that the carriers of the LPL SX genotype had significantly more negative oral fat tolerance test response (TG postprandial) 18 . However, the studies of Evans et al 19 and Shahzad et al 10 illustrated that the SX genotype of the LPL S447X was not associated with hyperlipidemia.…”
Section: Discussionmentioning
confidence: 98%